2022
DOI: 10.1038/s41598-022-22804-x
|View full text |Cite
|
Sign up to set email alerts
|

Secure secondary utilization system of genomic data using quantum secure cloud

Abstract: Secure storage and secondary use of individual human genome data is increasingly important for genome research and personalized medicine. Currently, it is necessary to store the whole genome sequencing information (FASTQ data), which enables detections of de novo mutations and structural variations in the analysis of hereditary diseases and cancer. Furthermore, bioinformatics tools to analyze FASTQ data are frequently updated to improve the precision and recall of detected variants. However, existing secure se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Concerning WGS storage and security issues, Tanjo et al suggested that the terabytes of data produced [ 20 ] will become easily and securely stored as new cloud systems technology is implemented [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning WGS storage and security issues, Tanjo et al suggested that the terabytes of data produced [ 20 ] will become easily and securely stored as new cloud systems technology is implemented [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the typical QKD network, which has limited functionality in supplying keys for confidential communication, the quantum secure cloud proposed by the National Institute of Information and Communications Technology implements a secret-sharing protocol [15] on a QKD network to achieve information-theoretically secure data transmission and storage [16][17][18].…”
mentioning
confidence: 99%